2023
DOI: 10.5603/fm.95513
|View full text |Cite
|
Sign up to set email alerts
|

A three-headed plantaris muscle fused with Kaplan fibers: potential clinical significance

Krystian Maślanka,
Nicol Zielinska,
Friedrich Paulsen
et al.

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Folia Morphologica" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…The three-headed PM is a very uncommon variant (only two reports), while the identi ed bipartite insertion has not been reported. Olewnik et al [12] and Maslanka et al [9] reports concerning the three-headed PM concluded a common tendon of the variant muscle, while in the current case, the two accessory heads had a bipartite insertion (lateral and medial attachments) via a short and distinct tendon into the calcaneal tendon and via a musculoaponeurotic expansion into the MFC.…”
Section: Discussionmentioning
confidence: 41%
See 3 more Smart Citations
“…The three-headed PM is a very uncommon variant (only two reports), while the identi ed bipartite insertion has not been reported. Olewnik et al [12] and Maslanka et al [9] reports concerning the three-headed PM concluded a common tendon of the variant muscle, while in the current case, the two accessory heads had a bipartite insertion (lateral and medial attachments) via a short and distinct tendon into the calcaneal tendon and via a musculoaponeurotic expansion into the MFC.…”
Section: Discussionmentioning
confidence: 41%
“…In this case, all head tendons created a common tendon [12]. Maslanka et al [9] identi ed a slightly different three-headed PM that fused into a common tendon, with a 1st head originating from the LFC and fused with Kaplan bers (another variant consisting of connections between the iliotibial band and the distal femur). The other two heads originated from the knee joint capsule and the LFC [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second one was originated from distal Kaplan fiber. In turn, the third and fourth heads were proximally attached to the lateral femoral epicondyle [9] . Knowledge about morphological variations is necessary because of their potential clinical significance.…”
Section: Introductionmentioning
confidence: 99%